Evaluation of Some Predictors of Metabolic Syndrome in an Important Group of Health Care Providers of Bangladesh (Bangladesh Journal of Medical Biochemistry, 2019)
Metabolic syndrome (MS), a global epidemic, is a cluster of risk factors for CHD, T2DM, stroke and other various medical problems, which affects specially those who lead sedentary and stressful life. Among the health service providers of Bangladesh, doctors are very important group who leads sedentary and mentally stressful life with low physical exercise. The aim was to evaluate WHR (waist-hip ratio), WHtR (waist-height ratio) and TG, HDL-C for their predictive value of MS. In this cross-sectional study, by convenient and purposive sampling technique, 25-55 years aged 500 Bangladeshi doctors (male 334, female 166) were enrolled. The study was carried out in the Department of Biochemistry, BSMMU, Shahbag, Dhaka, Bangladesh. MS was diagnosed by modified NCEP ATP III criteria. Prevalence of MS was measured at 95% CI. Statistical significance was set at p0.6) for their predictive value of MS; WHtR was revealed better than WHR as an index for MS (AUC 0.667 vs. 0.652 in male; 0.706 vs. 0.681 in female). It can be concluded, the prevalence of MS is very high among the doctors of Bangladesh; WHtR can be used as a good and relevant index for MS.Bangladesh J Med Biochem 2018; 11(1): 26-35